Multiple Cropping Systems for Improving Crop Yield and Reducing Environmental Costs - Xiaogang Yin; Zhenwei Song (Agronomy)
Multiple cropping, characterized as two or more crops planted in the same field either sequentially or simultaneously within a year [...]